Spark Plasma Sintering: Homogenization of the Compact Temperature Field for Non Conductive Materials. (19th November 2013) - Vanherck, Thierry; Jean, Guillaume; Gonon, Maurice; Lobry, Jacques; Cambier, Francis
Abstract : Spark Plasma Sintering presents many advantages in comparison with more conventional sintering techniques. Nevertheless, one of its main drawbacks is the heterogeneity of temperature field during the dwell of the temperature cycle, giving heterogeneous final microstructure. In this article, we propose to optimize the temperature field in the compact in order to obtain an almost homogeneous temperature only by modifying the tools dimensions. This optimization is based on the use of a coupled thermoelectric finite element model of the process. Finally, we present the sintering conditions influencing the optimization parameter.